PENINGKATAN KADAR ASAM LAKTAT DALAM DARAH SESUDAH BEKERJA - Irma Hidayah (Universitas Airlangga, 2018)
Fatigue is a protective mechanism of the body to avoid further damage resulting in the recovery after the break. It can occur because of a accumulation of lactic acid due to continuous muscle contraction. One of the jobs in Gunawangsa Tidar Superblock Apartment Project at PT. PP (Persero) Tbk. which can lead to fatigue is formwork jobs. The purpose of the study was to analyze the increased concentration of lactic acid in the blood after work on the formwork workers Gunawangsa Tidar Superblock Apartment Project at PT. PP (Persero) Tbk. This study was an observational study with cross-sectional study design. Data obtained by using interviews with questionnaires about sexs, ages, length of work, duration of work, duration of rest, work day and perception of heat exposure. Beside that, data wa collected by measuring lactic acid consentration in the blood with the Accutrend Plus Brand Roche to 30 formwork workers. The independent variable was working while dependent variable was concentration of lactic acid in the blood. Data were tested using Wilcoxon Signed Ranks Test. The results showed that the average concentration of lactic acid in the blood before and after work, namely 0.263 mmol/l and 0.883 mmol/l. Based on statistical test of Wilcoxon Signed Ranks Test, was obtained N Positive Ranks = 16 with Asymp. Sig. (2-tailed) = 0.001. The conclusion of this study that there is an increase in lactic acid consentration in the blood after work.Keywords: blood, fatigue, lactic acid